Peripheral Arterial Disease in Patients with Type 2 Diabetes Mellitus - Rhee, Sang Youl (Diabetes Metab J, 2015)
Peripheral arterial disease (PAD) in patients with type 2 diabetes mellitus (T2DM) exhibits broad clinical characteristics and various consequences and is known as one of the major macrovascular complications of T2DM. Atherosclerosis is recognized as the most direct and important cause of PAD, but acute or chronic limb ischemia may be the result of various risk factors. In light of the increasing number of patients who undergo peripheral vascular procedures, the number of subjects who are exposed to the risks for PAD and related complications is increasing. In this review, we will discuss the clinical and epidemiological characteristics of PAD, as well as the clinical significance of PAD in T2DM subjects.